An improvement in three-dimensional pure proportional navigation guidance - Shin, Hyo-Sang; Li, Ke-Bo (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper proposes an improved version of 3D pure proportional navigation (PPN) against a manoeuvring target. The main research hypothesis is that the performance of 3D PPN can be improved by properly selecting the direction of the guidance command as there exists an infinite number of potential directions complying with the PPN concept in 3D space. Analysis on the relative motion confirms the validity of the hypothesis and leads to the development of a new guidance algorithm. Unlike traditional 3D PPN, the guidance algorithm developed adapts the direction, but maintains the magnitude of the commanded acceleration proportional to only the line-of-sight (LOS) rate. The validity and performance of the proposed guidance algorithm are investigated through theoretical analysis and numerical simulations.
Keywords: 3D PPN; manoeuvring target; direction of commanded acceleration; relative motion analysis